Radiographic assessment of mandibular canal in Nepalese population: a study based on cone beam computed tomography images - Shrestha, Pragya; Mansur, Dil Islam; Humagain, Manoj; Koju, Sushmit; Maskey, Sunima (Journal of Chitwan Medical College, 2019)
Background: Mandibular canal runs in the body and ramus of mandible and provides passage for inferior alveolar nerve. Knowledge on spatial relationship of canal with adjacent structures prevent damage to nerve during surgical procedures. This study aims to find three-dimensional relationship of canal as well as its relation with third molar. Methods: This was a cross sectional and retrospective study conducted on Cone Beam Computed Tomography images. The relation and position of canal with third molar and position of canal in vertical and horizontal dimensions were analyzed. Results: Mandibular canal was found to be progressively descended in 43% of the canals. The canal was located apical to third molar in 61.9% cases and regarding contact relation, 121(56%) of the third molars had no contact with the canal. Buccal cortical plate was maximum at the level of distal root of second molar and minimum at the level of mesial root of first molar and was reverse for lingual cortical plate. The highest distance between upper border of canal and inferior border of mandible was at mental foramen 13.55±2.27 mm and lowest at mesial root of second molar, 8.72±2.59 mm. Minimum distance between superior border of canal and alveolar crest was distal to second molar (13.78±3.54 mm) and maximum between first molar and second premolar (17.91±3.08 mm). Conclusions: It was observed that canal was interradicularly placed and was by penetrated by third molar in some cases. Thickness of cortical plates varied in various locations buccally and lingually.